Komitmen Kelurahan Pagesangan Surabaya dalam Percepatan Penurunan Stunting - Rasyidah, Amira Farah; Farapti, Farapti (Media Gizi Kesmas, 2024)
Background: Stunting or failure to grow and develop had the impact to children who could experience impaired cognitive development and brain maturation which would affect learned achievement.  This condition was the impact of a decline in education, income, and productivity in adulthood.  In Pagesangan Subdistrict Surabaya, in 2022 seven children was stunted.  The Indonesian government targets the prevalence of stunting in 2024 have been 14%. Objectives: This research aims to determine the commitment of Pagesangan Subdistrict in accelerating stunting reduction. Methods: This qualitative research with a phenomenological approach has been able to understand and describe specific phenomena, in this case finding patterns of relationships between sub-district commitments to the acceleration of profound stunting reduction.  Then the essence of the participant's experience of a phenomenon was obtained. The locations for the FGD activities in this research was the Pagesangan subdistrict office, Kebonsari community health center, and Jambangan Surabaya district office. The sampling method was purposive sampling.  Data collection in this research was carried out on 10 – 12 November 2022. Results: Based on the results of the FGD (Forum Group Discussion), there had been a commitment from the Pagesangan Surabaya Subdistrict apparatus to accelerate the reduction of stunting.  The programs or activities that had been carried out in Pagesangan Subdistrict were accompanying prospective brides and grooms, Posyandu ASIK (smart healthy and creative children), providing food to toddlers.  stunting, and assistance to pregnant women. Conclusions: Efforts made by the government include a situation analysis carried out in Pagesangan Subdistrict which involved all instruments; village officials, health development cadres, assistant staff for stunting, PKK (family welfare development) and other parties.  To found out the level and commitment to accelerating stunting reduction in Pagesangan village, a joint discussion (FGD) was held to find out the causes and obstacles to accelerating stunting reduction.  From the FGD (forum group discussion) that was carried out, the results obtained were that Pagesangan Subdistrict Surabaya had made various efforts to resolve the occurrence of stunting.